A framework for assessing groundwater vulnerability and pollution risk in transboundary aquifers: Insights from the Estonian-Latvian transboundary area - Magdaleena Männik; Janis Bikše; Enn Karro; Andres Marandi (Journal of Hydrology: Regional Studies)
Study region: Estonian-Latvian transboundary area Study focus: The primary aim of this study is to develop and apply a harmonized framework for assessing groundwater vulnerability and pollution risk in the Estonian-Latvian transboundary area. The DRASTIC and modified DRASTIC methods were employed to evaluate natural vulnerability, while DRASTIC-L and modified DRASTIC-L methods were used to integrate land use and assess pollution risk. Sensitivity analyses were conducted to identify the influence of key parameters, and results were validated using pollutant infiltration time calculations. This multi-method approach addresses the region's geological complexity and incorporates anthropogenic impacts to provide a comprehensive assessment. New hydrogeological insights for the region: The study reveals significant spatial variability in groundwater vulnerability, influenced by sediment composition, groundwater level, and land use. High-risk areas are predominantly located in regions with sandy sediments, shallow groundwater, and intensive agricultural activity, while zones with deeper groundwater and clay-rich sediments show greater natural protection. By integrating pollution risk mapping with traditional vulnerability assessments, the study highlights the critical role of anthropogenic pressures in shaping contamination risks. The findings underscore the importance of harmonized cross-border data collection and provide a replicable framework for sustainable transboundary groundwater management. These insights contribute to protecting water resources and ensuring the availability of safe drinking water for present and future generations.